KERUKUNAN DAN KEARIFAN LOKAL DALAM HAK-HAK MASYARAKAT HUKUM ADAT KAMPAR - Erman, Afdhal Rinaldi (Lembaga penelitian dan pengabdian kepada masyrakat, 2012)
In the presence Regency custom society Kampar not most refures. They live years in emvironmentally which underpinned by over helmed natural resources support. They have region outhority as soiled as, forest and water per se it rich will subsistance source. Available reconciliation and local wisdom in one tatanan lives good apply to person, group even another society